El impacto en las exportaciones ecuatorianas hacia el Mercosur después de la firma Can-Mercosur. Periodo 1990-2015 - Torres Melo, Álvaro Stalin (2018)
Trade agreements that establish tariff preferences between similar countries generate positive results, although the effect on smaller economies is questioned. This research intends to verify if, in South America, trade agreements improve the exports of the smaller economies. To this end, the effects of the trade agreement between the CAN (Andean Community of Nations) and MERCOSUR (Common Market of the South) are analyzed by means of a gravitational model on Ecuadorian exports destined for MERCOSUR in the period 1990-2015. The result shows that the treaty of the CAN-MERCOSUR firm encouraged exports from Ecuador to member countries of the MERCOSUR bloc.